IMPACT OF SOCIAL CAPITAL ON CAREER DEVELOPMENT - Demirkıran, Canan Yıldırım; Gençer, Mehmet (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to explore the literature of social capital on career development. The various theoretical models drawn through social capital theory and the impacts derived on career progress are highlighted.Within this scope, the theoretical background and literature search on social capital and human capital management career development are deeply investigated. The major gaps within the literature, under this scope of social capital on human resources are identified. The social capital and hybrid theoretical frameworks are evaluated and suggestions for the future academic researchers have been described.One of the major findings of this research is that, it highlights the lack of hybrid theoretical models including social capital on career progress. The main proposition of social capital creating an advantage for accessing and utilizing career opportunities is verified through various researches with exceptions. Another identified gap was the commonality of the methodology as well as the commonalities of the professionals’ records under investigation. The professionals under focus had major commonalities like graduation from the same university or working for the same company and mainly the academia. The results of this work aims to enlighten the academic literature of social capital and career development with possible future research questions.